Rapid and Reversible Development of Axonal Varicosities: A New Form of Neural Plasticity - Gu, Chen (Frontiers in Molecular Neuroscience, 2021)
Axonal varicosities are enlarged, heterogeneous structures along axonal shafts, profoundly affecting axonal conduction and synaptic transmission. They represent a key pathological feature believed to develop via slow accumulation of axonal damage that occurs during irreversible degeneration, for example in mild traumatic brain injury (mTBI), Alzheimer’s and Parkinson’s diseases, and multiple sclerosis. Here this review first discusses recent in vitro results showing that axonal varicosities can be rapidly and reversibly induced by mechanical stress in cultured primary neurons from the central nervous system (CNS). This notion is further supported by in vivo studies revealing the induction of axonal varicosities across various brain regions in different mTBI mouse models, as a prominent feature of axonal pathology. Limited progress in understanding intrinsic and extrinsic regulatory mechanisms of axonal varicosity induction and development is further highlighted. Rapid and reversible formation of axonal varicosities likely plays a key role in CNS neuron mechanosensation and is a new form of neural plasticity. Future investigation in this emerging research field may reveal how to reverse axonal injury, contributing to the development of new strategies for treating brain injuries and related neurodegenerative diseases.